2015
DOI: 10.1002/pros.22999
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double‐blind placebo controlled phase I–II study on clinical and molecular effects of dietary supplements in men with precancerous prostatic lesions. Chemoprevention or “chemopromotion”?

Abstract: Administration of high doses of lycopene, GTCs, and selenium in men harboring HGPIN and/or ASAP was associated with a higher incidence of PCa at re-biopsy and expression of microRNAs implicated in PCa progression at molecular analysis. The use of these supplements should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 33 publications
3
41
0
1
Order By: Relevance
“…Resveratrol, ellagic acid or green tea catechins [3,4,50] have been previously shown to modulate miRNA expression in certain tissues. We here provide additional evidence that HT, the foremost polyphenol of extra virgin olive oil and a unique component of the Mediterranean diet, also modulates the expression of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, ellagic acid or green tea catechins [3,4,50] have been previously shown to modulate miRNA expression in certain tissues. We here provide additional evidence that HT, the foremost polyphenol of extra virgin olive oil and a unique component of the Mediterranean diet, also modulates the expression of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In a similarly designed study comparing EGCG extract versus placebo, a significant decrease was obtained only for the combined endpoint "carcinoma plus atypical small acinar proliferations" but not for prostate cancer alone [201]. Contrary to these results, Gontero et al [202] reported an increase in prostate cancer incidence in patients with high grade prostatic intraepithelial neoplasia (HGPIN) or atypical small acinar proliferations (ASAP), after supplementing the diet with selenium, lycopene and GTE.…”
Section: Prostatic Cancer-additional Evidencementioning
confidence: 91%
“…Biological and environmental factors are predominantly common to both tissue and circulating miRNAs. Multiple studies have highlighted that both external and patient-intrinsic -Study design -Develop standard procedures for specimen selection and handling -Review miRNA databases to select appropriate miRNAs for study -Avoid blood cell miRNAs -Account for environmental and biological preanalytic variables with appropriate case and control subjects -Document relevant preanalytic variables and deviations from standard procedures -Extraction -Common extraction method for all specimens -Normalization -Use exogenous "spike in" miRNA or validated endogenous miRNA factors such as age, sex, race, body mass index (BMI), diet, fasting state, underlying illnesses/organ dysfunction, blood cell count, exercise, vitamin supplementation, medications, smoking, diurnal variation, chemical exposure and even altitude can influence miRNA concentrations and are often difficult to standardize [2,13,[16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Common Pre-analytical Variables Common Biological/environmenmentioning
confidence: 99%